The Importance of Pronunciation in English Communication - Srakaew, Phra Narong (Journal of Asian Language Teaching and Learning (Online), 2021)
The purpose of this article is to present the importance of pronunciation in English communication. Pronunciation is one of the problems in the field of English language teaching as the second or foreign language. In many classes of English language, teaching pronunciation gets little attention. Whereas, pronunciation is a very important thing in the language, especially in speaking aspect but many teachers who teach foreign languages are not aware of it. Most of them do not give correct pronunciation when they are teaching. Certainly, it will cause learners to imitate the words spoken by the teacher with the wrong pronunciation as well. As the result of this problem, learners will experience the wrong pronunciation continuously in some words that are often spoken by the teacher. Why should we pay attention to pronunciation in speaking? The answer is so simple, it is because pronunciation is the most important thing when communicating with others. When we talk to other people with wrong pronunciation then it will cause misunderstanding so we have to be careful when pronounce a word.